52 tips for limit hold'em poker - Shulman, Barry (Cardoza Publishing, 2012)
The fifty-two tips--really fundamental playing concepts--are divided into six sections: Three universal Hold'em concepts; playing before the Flop; playing on the Flop; playing on the Turn; playing on the River, and more Hold'em concepts you should know.